Življenje kralja Petra II. Karađorđevića po drugi svetovni vojni v luči ohranjenih britanskih dokumentov - Blaž Torkar (Dileme)
Based on an analysis of British archival documents and published literature, this article discusses the life of Peter II Karađorđević, King of Yugoslavia, after the Second World War. In 1945, the king was deprived of all power as a ruler, and the Yugoslav monarch found himself in exile. He lived in the UK and France together with his family, and he spent his last years in the US. During his first years in exile, he drew attention to the fact that a communist dictatorship had taken over in Yugoslavia, hoping that there would be a change in power and that he would return home. The king also experienced problems in his private life and especially financial problems during the postwar period. Throughout, he sought to unify the Serbian emigrant organizations and bridge the schism in the Serbian Orthodox Church. He died of severe illness in 1970 and was buried at Saint Sava Monastery Church in Libertyville,not far from Chicago. In 2013, his remains and those of his family were transferred to the Royal Mausoleum at Oplenac, Serbia.